Stalin and the Lubianka: a documentary history of the political police and security organs in the Soviet Union, 1922-1953 - Shearer, David R. (Annals of communism, 2015)
"This fascinating documentary history is the first English-language exploration of Joseph Stalin's relationship with, and manipulation of, the Soviet political police. The story follows the changing functions, organization, and fortunes of the political police and security organs from the early 1920s until Stalin's death in 1953, and it provides documented detail about how Stalin used these organs to achieve and maintain undisputed power. Although written as a narrative, it includes translations of more than 170 documents from Soviet archives"--